Poor economics : barefoot hedge-fund managers, DIY doctors and the surprising truth abbout life on less than $1 a day - Banerjee, Abhijit V. (Peguin Books, 2012)
Why would a man in Morocco who doesn't have enough to eat buy a television? Why do the poorest people in India spend 7 percent of their food budget on sugar? This book overturns the myths about what it is like to live on very little, revealing the unexpected decisions that millions of people make every day